Comparison of Ultrasound-Guided Nerve Block with Ultrasound-Guided Nerve Stimulation Technique for Obturator Nerve Block in Transurethral Resection of Bladder Tumour - Ahmad, Mirza Sijeel; Khan, Umer; Haider, Syed Aftab; Sultan, Atqua; Khanum, Shazia; Saleemi, Muhammad Saleem (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the ultrasound-guided nerve block with ultrasound-guided nerve stimulation technique for obturator nerve block (ONB) in patients undergoing transurethral resection of bladder tumour (TURBT).Study Design: Prospective comparative study.Place and Duration of Study: Department of Anesthesiology, Nishtar Medical University/Hospital Multan from Jan to Jul 2019.Methodology: A total of 80 patients were divided into two groups. In Group-I, an ultrasound-guided nerve block was applied, while in Group-II, an ultrasound-guided nerve stimulation technique was applied for the block. Time of onset/ success of motor block and ease of approach were the primary study endpoints. At the same time, the surgeon and patient satisfaction were secondary endpoints.Results: Motor block onset time was 6.58±2.16 minutes in Group-II versus 12.41±2.39 minutes in Group-I (p-value